Educational attainment, growth and poverty reduction within the MDG framework: simulations and costing for the Peruvian case - Yamada Fukusaki, Gustavo (2007)
We propose a model that accounts for the potential feedback between schooling performance, human capital accumulation and long run GDP growth, and links these results with poverty incidence. Our simulation exercise takes into account targets for education indicators and GDP growth itself (as arguments in our planner’s loss function) and provides two conclusions: (i) with additional funds which amount to 1% of GDP each year, public intervention could add, by year 2015, an extra 0.89 and 1.80 percentage points in terms of long-run GDP growth and permanent reduction in poverty incidence, respectively; and (ii) in order to engineer an intervention in the educational sector so as to transfer households the necessary assets to attain a larger income generation potential in the long run, we need to extend the original set of MDG indicators to account for access to higher educational levels besides primary.